Transformations in the Family Institution during the Age of Occultation - Mehdi Mohammadzadeh Bani Tarfi; Hamidreza Mashhadi (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present study is to review transformation of the family institution before the reappearance of Imam Zaman (PBUH). The method of study is descriptive analysis and according to the narrations about transformations in family and society at the Age of Reappearance, the negative changes afflicting family at this age involve: Dissolution of ethics due to lack of rationality in family, secularism in families leading to the deterioration of the status and character of family members, freedom of women and the spread of feminist thoughts, negative transformation in the structure of family from traditional to modern, negligence in religious and spiritual upbringing of children. More negative transformations in the institution of family during the age of reappearance are as follows: Distancing from Mahdaviat culture and instructions due to lack of educating children in families as well as extremist materialism, the domination of worldly emotions or lack of rationality in families. With respect to the domino effect of ethical vices, if enough attention is paid to upbringing of children, other vices disappear in family and society as they will be replaced with virtues one after another.